2007
DOI: 10.1152/ajpheart.00008.2007
|View full text |Cite
|
Sign up to set email alerts
|

Impaired central hemodynamic response and exaggerated vasoconstriction during muscle metaboreflex activation in heart failure patients

Abstract: A. Impaired central hemodynamic response and exaggerated vasoconstriction during muscle metaboreflex activation in heart failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(185 citation statements)
references
References 51 publications
17
156
0
7
Order By: Relevance
“…This response is achieved as the result of an elevation in sympathetic tone, which produces arteriolar constriction and enhancement in myocardial performance and in cardiac preload (18,35,39). Differently, in several cardiovascular diseases, such as chronic heart failure and hypertension, although not universally reported (37,50), it has been demonstrated that excessive sympathetic activity can occur during the metaboreflex (7,11,16,41,42). This fact leads to detrimental effects, such as elevated SVR, which in turn causes excessive vasoconstriction and elevated blood pressure (46,47).…”
Section: The Main New Finding Of the Present Investigation Is That Obmentioning
confidence: 99%
See 2 more Smart Citations
“…This response is achieved as the result of an elevation in sympathetic tone, which produces arteriolar constriction and enhancement in myocardial performance and in cardiac preload (18,35,39). Differently, in several cardiovascular diseases, such as chronic heart failure and hypertension, although not universally reported (37,50), it has been demonstrated that excessive sympathetic activity can occur during the metaboreflex (7,11,16,41,42). This fact leads to detrimental effects, such as elevated SVR, which in turn causes excessive vasoconstriction and elevated blood pressure (46,47).…”
Section: The Main New Finding Of the Present Investigation Is That Obmentioning
confidence: 99%
“…An impedance device (NCCOM 3; BoMed, Irvine, CA) previously used in similar experimental settings was used (9,11,12). This technique assumes that when an electrical current circulates through the thorax, the pulsatile aortic blood flow causes a proportional fluctuation in electrical conductivity.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the limited ability to raise cardiac output during metaboreflex activation, the mechanism of the pressor response shifts from a flow-mediated rise in arterial pressure to peripheral vasoconstriction (18,35). What causes this shift is unclear but may involve impaired arterial baroreflex buffering of the metaboreflex pressor response.…”
Section: Impaired Baroreflex Buffering Of Muscle Metaboreflex In Hearmentioning
confidence: 99%
“…These data should also contribute to a better understanding of the pathophysiology of heart failure. Increasing evidence suggests the metaboreflex is exaggerated or tonically activated in heart failure (9,13,28) and that hypercapnia plays a key role (5,6,16,12) in the disease complications. Furthermore, because heart failure is characterized by an inability to increase SV, hemodynamic effects related to the interactions between the muscle metaboreflex and hypercapnia, such as those observed in this study, could explain in part the heart failure-linked exercise intolerance.…”
Section: Perspectives and Significancementioning
confidence: 99%